Study of EDC/NHS immobilization for plumbous detection using surface plasmon resonance - Alwahib, Ali Abdulkhaleq; Sadrolhosseini, Amir Reza; Lim, Hong Ngee; Yaacob, Mohd Hanif; Abu Bakar, Muhammad Hafiz; Mahdi, Mohd Adzir (Penerbit UTM Press, 2016)
The presence of plumbous (Pb2+) in Irrigation water is harmful for the environment as well as human health. Herein, a simple yet effective sensor for Pb2+ detection is presented utilizing a surface plasmon resonance technique. The proposed sensor consists of a combination of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) were attached to a gold layer offers a new option for heavy metal detection. The EDC/NHS works as a sensing layer that able to detect Pb2+ down to 15 ppm that matches with the United States Environment Protection Agency.